Regge Trajectories of Quark Gluon Bags - Bugaev, K.A.; Zinovjev, G.M. (Український фізичний журнал, 2010)
Using an exactly solvable statistical model, we discuss the equation of state of large/heavy and short-living bags of the quark gluon plasma (QGP).We argue that the large width of the QGP bags explains not only the observed deficit in the number of hadronic resonances, but also clarifies the reason why the heavy QGP bags cannot be directly observed even as metastable states in the hadronic phase. Also the Regge trajectories of large and heavy QGP bags are established both in vacuum and in a strongly interacting medium. It is shown that, at high temperatures, the average mass and width of the QGP bags behave in accordance with the upper bound of the Regge trajectory asymptotics (the linear asymptotics), whereas, for temperatures below Tн=2 (Tн is the Hagedorn temperature), they obey the lower bound of the Regge trajectory asymptotics (the square root one). Thus, for T < Tн=2; the spin of the QGP bags is restricted from above, whereas, for T > Tн=2, these bags demonstrate the standard Regge behavior consistent with the string models. Використовуючи точний розв’язок статистичної моделi, обговорено рiвняння стану великих/важких i короткоживучих мiшкiв кварк-глюонної плазми (КГП). Наведено аргументи того, що велика ширина мiшкiв КГП не тiльки пояснює дефiцит кiлькостi адронних резонансiв, але й причину того, що важкi мiшки КГП не можуть безпосередньо спостерiгатися навiть як метастабiльнi стани в адроннiй фазi. Також знайдено Редже траєкторiї великих i важких мiшкiв КГП як у вакуумi, так i в сильновзаємодiючому середовищi. Доведено, що за високих температур середня маса i ширина мiшкiв КГП пiдкорюються верхнiй границi асимптотики траєкторiї Редже (лiнiйна асимптотика), тодi як для температур, нижчих за Tн=2 (Tн – температура Хагедорна), вони пiдкорюються нижнiй границi асимптотики траєкторiй Редже (асимптотика кореня квадратного). Таким чином, для T < Tн=2 спiн мiшкiв КГП обмежено зверху, тодi як для T > Tн=2 цi мiшки демонструють стандартну Редже поведiнку, яка узгоджується з моделями струн.